Reconstruction of Ius Constituendum Cyber Notary Regulations in E-RUPS as Relaas Acta - Shicilya, Wanda; Souissa, Marsella Maurin; Kusuma, Rizka Tiara; Wesna, Putu Ayu Sriasih (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
The purpose of this study is to examine the reconstruction of the ius constituendum regulating cyber notary in E-RUPS as a relaas acta with 2 problems, namely the urgency of regulating cyber notary as the legal basis for making E-RUPS and the draft ius constituendum regulating cyber notary in the future. This study uses a normative legal research method in the form of a legislative approach. The results of the study indicate that there is uncertainty in the legal regulation of cyber notary in Indonesia regarding E-RUPS whose deeds are made by a notary as a relaas acta, so a draft legislation is needed as a legal basis for cyber notary in the future to guarantee the validity of an authentic deed.